Terrestrial contributions to Afrotropical aquatic food webs: The Congo River case. Issue 18 (27th August 2019) - Soto, David X.; Decru, Eva; Snoeks, Jos; Verheyen, Erik; Van de Walle, Lora; Bamps, Jolien; Mambo, Taylor; Bouillon, Steven
Abstract: Understanding the degree to which aquatic and terrestrial primary production fuel tropical aquatic food webs remains poorly understood, and quantifying the relative contributions of autochthonous and allochthonous inputs is methodologically challenging. Carbon and nitrogen stable isotope ratios ( δ 13 C, δ 15 N) can provide valuable insights about contributions of terrestrial resources and trophic position, respectively, but this approach has caveats when applied in typical complex natural food webs. Here, we used a combination of C, N, and H ( δ 2 H) stable isotope measurements and Bayesian mixing models to estimate the contribution of terrestrial (allochthonous) and aquatic (autochthonous) inputs to fish and invertebrate communities in the Congo River (and some tributaries). Overall, our results show that we gained power to distinguish sources by using a multiple tracer approach and we were able to discriminate aquatic versus terrestrial sources (esp. including hydrogen isotopes). Fish δ 2 H values were clearly correlated with their food preferences and revealed a high level of variation in the degree of allochthony in these tropical aquatic communities. At the community level, it is clear that terrestrial C3 plants are an important source fueling the Congo River food web. However, in order to better constrain source contribution in these complex environments will require more robust constraints on stable isotope values of algal and methane‐derived C sources. Abstract : Our study points toward a general significance of terrestrial C3 plants (allochthonous sources) for the fish and invertebrate communities in Afrotropical systems such as the Congo River basin. However, results showed a high variability of allochthony within communities of this large tropical aquatic system.